2010
DOI: 10.1091/mbc.e09-08-0655
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Cyclic Adenosine 3′,5′-Monophosphate at the Plasma Membrane Clusters PDE3A and Cystic Fibrosis Transmembrane Conductance Regulator into Microdomains

Abstract: PDE3A functionally and physically interacts with CFTR. Inhibition of PDE3A generates compartmentalized cAMP, which further clusters PDE3A and CFTR into microdomains at the plasma membrane of epithelial cells and potentiates CFTR channel function. Our findings provide insights into the important role of PDE3A in compartmentalized cAMP signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 67 publications
7
97
1
Order By: Relevance
“…Inhibition of PDE4, but not PDE1, stimulated Cl -secretion by ADPKD cells (Figure 3) and promoted cyst-like dilations in Pkd1 2 /2 mouse embryonic kidneys ( Figure 4). Although PDE3 has been shown to be functionally coupled to Cl -secretion by shark rectal glands 41 and pig trachea submucosal glands, 42 we found that PDE3 inhibition had only a modest effect on Cl -secretion by ADPKD cells, similar to human bronchial epithelial cells. 43 These findings point to PDE4 as the principal isoform controlling the cAMP pool involved in Cl --dependent fluid secretion by ADPKD cells.…”
Section: Discussioncontrasting
confidence: 58%
“…Inhibition of PDE4, but not PDE1, stimulated Cl -secretion by ADPKD cells (Figure 3) and promoted cyst-like dilations in Pkd1 2 /2 mouse embryonic kidneys ( Figure 4). Although PDE3 has been shown to be functionally coupled to Cl -secretion by shark rectal glands 41 and pig trachea submucosal glands, 42 we found that PDE3 inhibition had only a modest effect on Cl -secretion by ADPKD cells, similar to human bronchial epithelial cells. 43 These findings point to PDE4 as the principal isoform controlling the cAMP pool involved in Cl --dependent fluid secretion by ADPKD cells.…”
Section: Discussioncontrasting
confidence: 58%
“…PDEs have been shown to play a key role in the spatial control of cAMP-PKA signalling in a number of cell systems, including airway epithelial cells, where both PDE3 (Penmatsa et al, 2010) and PDE4 have been suggested to contribute to the local modulation of cAMP levels that control CFTR activity (Barnes et al, 2005). Although PDE activity has been shown to be sufficient to restrict cAMP diffusion to defined subcellular compartments in certain cell types (Oliveira et al, 2010;Terrin et al, 2006), it has been argued that the densely packed subcortical cytoskeleton might constitute an efficient barrier to cAMP diffusion and promote compartmentalized cAMP and PKA signals by allowing cAMP to accumulate locally to a level sufficient to activate PKA, while preventing activation of PKA in the bulk cytosol (Rich et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we reasoned that MAST205 may be involved in biosynthesis or intracellular trafficking of CFTR. To test whether MAST205 participates in CFTR trafficking, we measured the CFTR cell surface expression upon transfection with MAST205 by using a surface labeling assay (30). We observed that overexpression of MAST205 increased the cell surface pool of CFTR protein by at least 20% (Fig.…”
Section: Cftr Interacts With Mast205-mentioning
confidence: 97%
“…Surface Labeling Assay-The expression of CFTR at the plasma membrane was determined by using surface labeling assay (30). Briefly, the transfected cells were fixed with 3.7% formaldehyde for 10 min, blocked with 1% BSA for 30 min, and treated with ␣-FLAG-HRP for 90 min.…”
Section: Real-time Rt-pcr Analysis Of Cftr Mrna Level Uponmentioning
confidence: 99%